Communication Strategy In Promoting Lapasi Beach Tourism Destination as a Container For Local Culture Preservation In West Halmahera - Saleh, Zulkifli Hi; Artha, Sarni (Jurnal Mamangan, 2024)
The development coastal areas as tourist destinations in Indonesia tends to increase along with the growing tourism sector. The development of these coastal areas also showcases the unique characteristics of each region as viable alternatives. Lapasi Beach is one of the coastal areas located in Lako Akelamo Village, Sahu District, West Halmahera Regency, North Maluku, which develops the tourism sector with its regional characteristics. The local community still firmly holds onto their culture, from their way of life and arts to their customs and traditions passed down through generations, which still exist to this day. The intention of this research is to understand the communication strategies in promoting Pantai Lapasi as a medium for preserving the local culture of West Halmahera. The method employed in this research is qualitative with a descriptive approach. According to the research outcomes, it shows that various communication strategies in promoting Pantai Lapasi as a medium for preserving the local culture of West Halmahera, among others, through the Beach Festival, social media (Facebook, YouTube, Instagram, WhatsApp flyers), and collaboration with stakeholders. However, the communication strategy in the promotion that has been carried out is still not effective, due to the lack of a proper marketing approach, limited human and financial resources, and the truancy of a good division of roles between the managers and the village government.